Precision Long-Chain Branched Polyethylene via Acyclic Diene Metathesis Polymerization (2015)
A series of polyethylenes containing 21-carbon alkyl branches have been synthesized by acyclic diene metathesis (ADMET) polymerization. These 21-carbon alkyl branches are precisely placed on every 15th, 19th, 21st, 23rd, and 39th carbon along the polymer backbone. Precision of primary structures of all polymers is verified by 1H and 13C NMR spectroscopy. All polymers present well-defined melting profiles, even at a high branch incorporation (13.3% mol). The melting temperature increases as the branch frequency decreases, similar to what we observed for short-chain branched polyethylenes. These observations together with a good linear relationship derived from Flory's theory suggest the exclusion of 21-carbon side chains from polyethylene crystal units.